Effect of the bound nucleon form factors on charged-current neutrino-nucleus scattering - Tsushima, K.; Kim, H.; Saito, K. (American Physical Soc, 2004)
We study the effect of bound nucleon form factors on charged-current neutrino-nucleus scattering. The bound nucleon form factors of the vector and axial-vector currents are calculated in the quark-meson coupling model. We compute the inclusive C-12(nu(mu),mu(-))X cross sections using a relativistic Fermi gas model with the calculated bound nucleon form factors. The effect of the bound nucleon form factors for this reaction is a reduction of similar to8% for the total cross section, relative to that calculated with the free nucleon form factors.